STUDI LABORATORIUM UJI TOKSISITAS ISOLAT Bacillus thuringiensisisraelensis DALAM MEDIA AIR PERASAN SINGKONG TERHADAP LARVA NYAMUK Aedes aegypti - Wulan Kusuma Jati; M. Arie Wuryanto; Dwi Sutiningsih (Jurnal Kesehatan Masyarakat (Undip), 2015)
Bacillus thuringiensis israelensis is a toxic bacteria for Aedes aegypti. However, raw materials of media for biopesticide production still imported . So, we need an alternative grower media, one of them by using the juice of cassava.The purpose was to determine the toxicity of B. thuringiensis israelensis isolates were cultured in the cassava juice against larvae of Ae. aegypti. This type of research is experimental research with posttest - only control group design. The population in this study were all third instar larvae of Aedes aegypti. Parameters observed that the number of spores of Bacillus thuringiensis israelensis were grown on cassava juice and mortality LC50 and LC90 of Ae. aegypti with probit regression analysis . The concentration used in toxicity tests is 0,89 x10-3 ppm; 1,30 x10-3ppm; 1,49 x10-3ppm; 1.69 x10-3 ppm; x10-3 2,20 ppm ; 3,22 x10-3 ppm and 5,43 ppm x10-3. The results showed the number of spores that grow on the medium cassava juice of 1 % 230 x105 spores / ml . LC50 and LC90 concentration of B. thuringiensis  israelensis which 3,674 x10-3ppm and 14,254 x10-3 ppm. From this study it can be concluded that B. thuringiensis israelensis were cultured in the cassava juice toxic to the larvae Ae . aegypti.